GNSS Meteorology for Disastrous Rainfalls in 2017–2019 Summer in SW Japan: A New Approach Utilizing Atmospheric Delay Gradients - Arief, Syachrul; Heki, Kosuke (Frontiers in Earth Science, 2020)
We studied disastrous heavy rainfall episodes in 2017-2019 summer in SW Japan, especially in the Kyushu region using tropospheric delay data from the dense Global Satellite Navigation System network GEONET (GNSS Earth Observation Network). This region often suffers from extremely heavy rains associated with stationary fronts during summer. In this study, we first analyze behaviors of water vapor on July 6, 2018, using tropospheric parameters obtained from the database at University of Nevada Reno. The data set includes tropospheric delay gradient vectors (G), as well as zenith tropospheric delays, estimated every 5 minutes. At first, we interpolated G to obtain those at grid points and calculated their convergence, similar to the quantity proposed by Shoji (2013) as water vapor concentration index. We obtained zenith wet delay from ZTD by removing zenith hydrostatic delay. The raw ZWD values do not really reflect the wetness of the atmosphere above the GNSS station because they largely depend on the station altitudes. To study the dynamics of water vapor before heavy rains, we estimated ZWD converted to the values at sea-level. In the inversion scheme, we used G at all GEONET stations and ZWD data at low-altitude (< 100 m) GEONET stations as the input. Then we assumed that spatial change of ZWD is proportional to G (e.g. Gx = H ZWD/x, where H is the water vapor scale height) and estimated sea-level ZWD at grid points all over Japan. At last, we tried to justify our working hypothesis that heavy rain occurs when both WVC and sea-level ZWD are high by analyzing hourly water vapor distributions in all the days in July 2017, July 2018, and August 2019. We found that both two values showed maxima in the studied period when three heavy rainfall (> 50 mm/hour) events occurred, i.e., July 5, 2017, July 6, 2018, and August 27, 2019. Next, we performed high time resolution analysis (every 5 minutes) on the days of heavy rain. The results suggest that both WVC and sea-level ZWD go up prior to the onset of the rain, and ZWD decreases rapidly once the heavy rain started.